Acting on behalf of the Bohemian King: Ferdinand Ernst von Waldstein’s Journey to Westphalia (1645–1647) (Theatrum historiae, 2017)
Ferdinand Ernst von Waldstein participated within the imperial delegation at the peace negotiations in Münster and Osnabrück where together with Georg von Plettenberg he represented the interests of Ferdinand III as the King of Bohemia at the Electoral College. Although he only took part in discussions that concerned one specific disputed issue, namely the return of the electoral vote to the Count Palatine of the Rhine, his presence at the meeting represents important evidence about the relations between the Czech Lands and the Holy Roman Empire during the period prior to the readmission of the Bohemian Elector and his representatives to the Electoral College, which occurred as late as in 1708. That mission also had an impact on the career of the young Waldstein, who, after his return, was introduced to the Aulic Council and from 1650 onwards another career awaited him in the Bohemian provincial offices and even there he was still performing tasks that were associated with the imperial policy.
Keywords: The Peace of Westphalia; the Bohemian electoral vote; imperial diplomac; Ferdinand Ernst von Waldstein; the Electoral College; the Electoral Palatinate